SPANISH EFL TEACHERS AND ICT TOOLS. A SURVEY-BASED ANALYSIS - Nerea; Mañoso-Pacheco, Lidia (Revista Inclusiones, 2020)
In the last few years, teachers in Spain have experienced numerous changes in their methodology due to the implementation of ICT (Information and Communication Technologies) in education. This research provides a survey-based analysis of EFL (English as a Foreign Language) teachers that assesses their attitude towards digital resources and the current state of affairs in Spain concerning digital tools. Results indicate that despite receiving training in digital skills, teachers still need more support from their educational centres and that the technical equipment available is limited. Besides, they use more often ICT tools for practicing listening and evaluate favourably collaboration among teaching staff and the figure of the ICT coordinator.